2017
DOI: 10.1158/0008-5472.can-16-2320
|View full text |Cite
|
Sign up to set email alerts
|

NR4A3 Suppresses Lymphomagenesis through Induction of Proapoptotic Genes

Abstract: Nuclear orphan receptor NR4A1 exerts an essential tumor suppressor function in aggressive lymphomas. In this study, we investigated the hypothesized contribution of the related NR4A family member NR4A3 to lymphomagenesis. In aggressive lymphoma patients, low expression of NR4A3 was associated with poor survival. Ectopic expression or pharmacological activation of NR4A3 in lymphoma cell lines led to a significantly higher proportion of apoptotic cells. In a mouse NSG xenograft model of lymphoma (stably transduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…Dysfunction and death of chondrocytes would lead to the failure of articular cartilage . Previous studies showed that NR4A3 is involved in promoting apoptosis in lymphoma and cancer cells by acting as downstream of P53 . Here, our data demonstrated this similar function of NR4A3 in rat chondrocytes (Figure and Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…Dysfunction and death of chondrocytes would lead to the failure of articular cartilage . Previous studies showed that NR4A3 is involved in promoting apoptosis in lymphoma and cancer cells by acting as downstream of P53 . Here, our data demonstrated this similar function of NR4A3 in rat chondrocytes (Figure and Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, germinal centre B-cells were included as non-neoplastic control and isolated from tonsils from young patients undergoing routine tonsillectomy as described in detail by our research group [50,51]. obtained as colorless solid with a yield of 36%.…”
Section: Patients' Samplesmentioning
confidence: 99%
“…Total RNA from fresh frozen DLBCL patient tissues, non-neoplastic germinal centre B cells and lymphoma cell lines were isolated and cDNA synthesis was performed as previously described by our research group [50,51]. Real-time semi-quantitative PCR (RQ-PCR) for CXCR4, CXCR7, CXCL12, Germany; assays and primers are listed in Table S1) was also performed as previously described [50,51].…”
Section: Rna Extraction and Rq-pcrmentioning
confidence: 99%
See 2 more Smart Citations